Prediction of three-dimensional crack propagation paths taking high cycle fatigue into account (Fracture and Structural Integrity, 2015)
Engine components are usually subject to complex loading patterns such as mixed-mode Low Cycle Fatigue Loading due to maneuvering. In practice, this LCF Loading has to be superimposed by High Cyclic Fatigue Loading caused by vibrations. The changes brought along by HCF are twofold: first, the vibrational cycles which are superposed on the LCF mission increase the maximum loading of the mission and may alter the principal stress planes. Secondly, the HCF cycles themselves have to be evaluated on their own, assuring that no crack propagation occurs. Indeed, the vibrational frequency is usually so high that propagation leads to immediate failure. In the present paper it is explained how these two effects can be taken care of in a standard LCF crack propagation procedure. The method is illustrated by applying the Finite Element based crack propagation software CRACKTRACER3D on an engine blade.
Keywords: Crack propagation; Mixed-mode; High cycle fatigue